Are Podcast Advertisements Effective? An Emerging Economy Perspective. Issue 2 (15th March 2023) - Bezbaruah, Subhalakshmi; Brahmbhatt, Kuldeep
Abstract: The evolution and consumers' acceptance of podcasts has been on the rise. Scholars argue that this rapid rise is due to the ability of podcasts to offer content that consumers find valuable. This has resulted in brands following consumers on the podcast platforms and attempting to reach them through podcast advertisements. The last decade has seen a tremendous rise in the podcast advertising budgets of brands. However, the nature of such podcast advertisements and their effect on consumer-brand relationships and behavioral intention are understudied. The present study explored the efficacy of podcast advertisements by utilizing the theoretical framework of advertising value and their effect on attitude toward Ads (AaD), attitude toward brand (AB), formation of purchase intent, and brand eWOM. The moderating role of the ad placement, through pre, post, and mid roll podcast advertisements, was observed while assessing the effect of podcast advertising on AaD. Data was collected through a structured survey instrument; in total, 389 millennial consumer responses were obtained. SmartPLS3 software was used for data analysis. The results empirically established that podcast advertisements were effective in creating consumer-brand relationships, while informative podcast ads were the most effective of the lot.